Hubungan Authoritarian Parenting Terhadap Gangguan Psikosomatik pada Mahasiswa dalam Penyusunan Tugas Akhir Skripsi - Karina Sefia Ananda; Kusnadi Kusnadi; Lena Marianti (Journal of Society Counseling, 2023)
This thesis is entitled "The Relationship of Authoritarian Parenting to Psychosomatic Disorders in Students in Preparing Their Final Thesis Assignments". The background is Authoritarian Parenting or authoritarian parenting towards Psychosomatic Disorders experienced by students in preparing their final assignments. Psychosomatic disorders are a term that refers to complaints of physical symptoms that arise due to psychological factors. Final year students who are working on their thesis, how can they complete their thesis on time, if there is no support from those closest to them. Authoritarian Parenting is a parent's authoritarian parenting style by setting absolute standards that children must follow. This research aims to determine the description of authoritarian parenting in students when preparing their final thesis assignment, the description of psychosomatic disorders in students in preparing their final thesis assignment and the relationship between Authoritarian Parenting and Psychosomatic Disorders in Students in Preparing their Final Thesis Assignment. This research uses a quantitative approach with a correlational method. The subjects in this research were a population of 104 respondents and a sample of 36 respondents, sampling was taken using the Simple Random Sampling Technique. Data collection techniques use questionnaire and documentation methods. The data analysis technique uses the Pearson Produst Moment test with the help of the From Windows SPSS Version 22 program. The results of the research show firstly, that the depiction of authoritarian parenting among students preparing their final thesis assignments is at a medium level with a percentage of 64% for 23 people. Second, the description of psychosomatic disorders in students preparing their final thesis assignments is at a moderate level with a percentage of 67%, as many as 24 people. And thirdly, it is known that the Asymp sig. (2-tailed) result is 0.001, the value is 0.001 < 0.05, so it can be concluded that Ha is accepted and H0 is rejected, which means that there is a relationship between authoritarian parenting and psychosomatic disorders in students in preparing their final thesis assignments with a relationship value of 0.733. in a strong relationship and has a positive relationship direction.